FAKTOR PENENTU KINERJA PERUSAHAAN FOOD AND BEVERAGE DI BEI PERIODE 2014-2017 - MICHAEL HIDAYAT; IGNATIUS RONI SETIAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to examine the effect of company’s solvency, total asset turnover, and family ownership on firm performance in food and beverage companies listed on the Indonesia Stock Exchange during the 2014–2017 period. The study employs a quantitative approach using purposive sampling and multiple linear regression analysis. The sample consists of 3 companies selected from a population of 13 companies, resulting in 48 observations. The results indicate that company’s solvency, total asset turnover, and family ownership have a positive and significant effect on firm performance. These findings suggest that firms with stronger financial conditions, more efficient asset utilization, and higher family ownership tend to achieve better performance. This study provides empirical evidence regarding the determinants of firm performance in the Indonesian food and beverage industry.